Microplastics mediates the spread of antimicrobial resistance plasmids via modulating conjugal gene expression - Qiu E. Yang; Zhenyan Lin; Dehao Gan; Minchun Li; Xuedan Liu; Shungui Zhou; Timothy R. Walsh (Environment International)
Antimicrobial resistance (AMR) and environmental degradation are existential global public health threats. Linking microplastics (MPs) and AMR is particularly concerning as MPs pollution would have significant ramifications on controlling of AMR; however, the effects of MPs on the spread and genetic mechanisms of AMR bacteria remain unclear. Herein, we performed Simonsen end-point conjugation to investigate the impact of four commonly used MPs on transfer of clinically relevant plasmids. The transfer breadth of a representative pA/C_MCR-8 plasmid across bacterial communities was confirmed by the cell sorting and 16S rRNA gene amplicon sequencing. Our study shows that exposure to four commonly found MPs promotes the conjugation rates of four clinically relevant AMR plasmids by up to 200-fold, when compared to the non-exposed group and that the transfer rates are MP concentrations demonstrate a positive correlation with higher transfer rates. Furthermore, we show that MPs induce the expression of plasmid-borne conjugal genes and SOS-linked genes such as recA, lexA, dinB and dinD. High-throughput sequencing of the broad transmission of plasmid pA/C_MCR-8, shows distribution over two main phyla, Pseudomonadota (50.0 %-95.0 %) and Bacillota (0.4 %-2.0 %). These findings definitively link two global health emergencies − AMR and environmental degradation via MPs, and to tackle global AMR, we must also now consider plastic utilisation and waste management.